2011
DOI: 10.2223/jped.2064
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HAART on growth and hospitalization rates among HIV-infected children

Abstract: Objective: To evaluate HAART-associated changes in growth and hospitalization rates over time in a cohort of HIV-infected children. Methods:Children starting HAART were assessed during the first 3 years of therapy. Clinical response was assessed every 24 weeks by z scores of weight-for-age and height-for-age. Linear regression models were used to detect predictors of clinical response. Pertinent information on hospitalizations was obtained retrospectively through review of medical records.Results: A total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
(39 reference statements)
1
6
0
Order By: Relevance
“…This research finding also disclosed comparable weight recovery between the two wings of treatment category at three and six months of ART which is also in compatible with other research findings (Abebe, 2017). Weight gain of greater than 10% at six months of ART was demonstrated in 44% of the patients in our study which was in consistence with the study from Brazil which showed mean weight-for-age z scores increment from -1.62 (±1.32) at baseline to -1.14 (±1.12) weight-for-age z scores at week 24 (Diniz, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…This research finding also disclosed comparable weight recovery between the two wings of treatment category at three and six months of ART which is also in compatible with other research findings (Abebe, 2017). Weight gain of greater than 10% at six months of ART was demonstrated in 44% of the patients in our study which was in consistence with the study from Brazil which showed mean weight-for-age z scores increment from -1.62 (±1.32) at baseline to -1.14 (±1.12) weight-for-age z scores at week 24 (Diniz, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…Age at ART initiation impacted on growth improvement: Children older than 3 years experienced a lower weight and height increase than younger children, and this resulted in better BMI outcome in infants, while height outcomes did not differ across age groups. Previous studies consistently describe improved weight outcomes for younger children [16,18,21,22,24,26,[35][36][37][38], possibly related to less severe gastrointestinal impairment and shorter duration of chronic immune activation [39,40]. Reports on the impact of age on height differ between studies, with improved height outcomes with younger age in some studies [23,24,26,35], while others reported no difference [36] or worse height outcomes for younger children [20,22].…”
Section: Discussionmentioning
confidence: 97%
“…ART has a positive effect on weight and, to a lesser extent, on height growth . As opposed to studies from developed countries [10,11,27], reports from developing countries have not shown normalisation of growth parameters [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. These studies, however, generally had relatively short follow-up periods of up to 2 years and were hampered by substantial loss to follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…In another Thai study, (5,11) the incidence of hospitalization was found to be 30.7% in the first six months of life, declining to 2.0% by the third year of life. A Brazilian study (6,12) found that 43.3% of children were hospitalized in the first three years of therapy. Although investigators have looked into the patterns and causes of hospitalization in children, there are little or no published studies investigating predictors of hospitalization in children on HAART.…”
Section: Introductionmentioning
confidence: 99%